Girassol - Souza, Andreia Ferreira de; Moreira, Iris Vania Aparecida; Rodrigues, Maria Aparecida Silva; Silva, Rinaldo Gomes da; Botassin, Rosa Maria Ferreira; Santos, Rosivania Cristina dos; Rodrigues, Silvina Souza da Silva; Reboli, Zelia Pereira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2022)
>>> ver pdf